PENINGKATAN PENDAPATAN ASLI DAERAH MELALUI ANALISIS EFEKTIFITAS DAN KONTRIBUSI RETRIBUSI PASAR - Dwiningwarni, Sayekti Suindyah; Suharsono, Judi; Dedy Eko TS, Mohammad (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2019)
The motivation of this study is the research conducted by Yuyus Yudistria (2015), which states that retribution is a potential income for a region. This study aims at 1) to determine the effectiveness of market retribution on Regional Original Revenue; 2) to determine the effect of market retribution contribution to Regional Original Revenue. The analytical method is multiple linear regression analysis. The results of the study include: 1) The overall average shop and lesehan retribution during the period 2010-2013 is very effective with values ​​above 100%, which is between 103% - 136%; 2) The overall average shop and lesehan retribution during the 2014 period is effective with a value between 90-100%, which is 97%; 3) Shophouse contributions have a positive and significant effect on PAD; 4) Lesehan contribution has a negative and significant effect on PAD partially; 5) The contribution of shophouses and lesehan has a positive and significant effect on PAD simultaneously. This indicates that there is still a lack of government intervention in service and upgrading of facilities to increase retribusi for shophouses and financial services as well as not yet optimal withdrawal of these levies. This levy provides positive hope for increasing PAD